Linguistic strategies for professional politeness among aspiring managers: An analysis of organizational psycholinguistics - Vlasenko, Olena; Maistruk, Viktoriia (East European Journal of Psycholinguistics, 2023)
In order to effectively communicate in a professional setting, it is essential for managers to have a mastery of the language specific to their field. One tool that can be used for professional communication is verbal politeness, which involves using appropriate words and phrases to show respect for the listener and soften unfavourable information. These linguistic units promote a culture of professionalism and ethical business relationships and are a key indicator of a manager’s speech competence. A psycholinguistic study examined the usage of polite language by aspiring managers. The participants were 218 undergraduate and graduate students enrolled in the Management program across various universities in Ukraine’s oblasts. The organizational psycholinguistics research aimed to assess the extent to which aspiring managers incorporate professional language units such as polite words and phrases in their speech. We analyzed the references of 1,308 respondents to determine how politeness language units corresponded to the structural parts of the document. By studying 928 selected language units of politeness, we could assess the level of politeness markers. This indicator reflects future managers’ skill level in applying synonymous ranges of politeness. The analysis found that respondents used various linguistic units to soften the impact of unfavourable information when conveying it to others. These units formed synonymous ranges based on context and semantic content. Only half of the students showed a wide range of knowledge and skills in appropriately using polite language. Thus, aspiring managers need to improve their knowledge and practical skills in using a variety of linguistic units of politeness in business documents. Therefore, we recommend implementing programs to improve communication levels for those pursuing higher education in management. Disclosure Statement No potential conflict of interest was reported by the authors. * Corresponding author: Olena Vlasenko, 0000-0002-1011-1965 vlasenkoolena@ieu.edu.ua